Harnessing animal model and computational experiments to discover antidiabetic compounds in Ficus racemosa - Mohammad Uzzal Hossain; A. B. Z. Naimur Rahman; Md. Shahadat Hossain; Shajib Dey; Zeshan Mahmud Chowdhury; Arittra Bhattacharjee; Ishtiaque Ahammad; Mohammad Kamrul Hasan; Istiak Ahmed; Md. Billal Hosen; Keshob Chandra Das; Chaman Ara Keya; et al. (BMC Complementary Medicine and Therapies)
Abstract Background Diabetes mellitus (DM) is a major health concern caused by poor blood sugar regulation. Despite oral hypoglycemic medications, diabetes and its complications remain clinically serious. Using animal models and in silico research, the antidiabetic potential of Ficus racemosa (F. racemosa) has been assessed in this study. Materials and methods The methanol extract of F. racemosa fruits was prepared using suitable methods. After injecting Alloxan (150 mg/kg) into Swiss Albino mice to cause diabetes, both diabetic and non-diabetic animals underwent OGTT and acute toxicity testing. The antihyperglycemic action was assessed by administering oral doses of 300 and 500 mg/kg of the methanol extract of F. racemosa fruit, as well as 5 mg/kg of glibenclamide. Subsequently, in silico techniques such as ADMET profiling, molecular docking, and simulations were employed. Results The findings from this study suggest that mice have tolerated doses under 3000 mg/kg without death or side effects. In mice model, both doses of F. racemosa extracts effectively reduced blood glucose (BGL) after 7 days of oral administration. Molecular docking and simulations demonstrated that the SIRT1 receptor had a greater affinity for friedelin, lupeol acetate, gluanol, and ferulic acid. The molecular dynamics demonstrated that all the compounds are stable to the receptors, as revealed by RMSD, RMSF, Rg and SASA parameters. Conclusion This study found that F. racemosa fruit extract significantly reduced hyperglycemia. Furthermore, four compounds may significantly contribute to the treatment of diabetes by reducing blood glucose levels. Thus, the findings of the current study may strengthen future research in the identification of antidiabetic compounds.